Peningkatan Kinerja Karyawan: Peran Kepemimpinan Transformasional, Disiplin Kerja dan Lingkungan Kerja Fisik - Wardani, Sri; Kawiana, I Gede Putu; Mahayasa, I Gede Aryana (Business Management Journal, 2024)
The purpose of this research is to determine and analyze the influence of transformational leadership, work discipline and physical work environment on employee performance. The population in this study were employees of the Ubung Denpasar Subdistrict Office with a total of 32 employees. The sample was determined using a non-probability sampling method with a saturated sample technique of 32 respondents. Data were analyzed using multiple linear regression analysis. The results of the analysis show that transformational leadership has a positive and significant effect on employee performance, work discipline has a positive and significant effect on employee performance and the physical work environment has a positive and significant effect on employee performance at the Ubung Denpasar Village Office Secretariat. Suggestions that can be put forward to the Ubung Denpasar Village Office Secretariat are that leaders can take a personal approach to employees in order to build better communication, clarify the duration of work on each job and improve employee work space arrangements at the Ubung Denpasar Village Office Secretariat.